Optimal torque control of an integrated starter–generator using genetic algorithms. (June 2015) - McGehee, Jeffery; Yoon, Hwan-Sik
A mild hybrid electric vehicle is a type of hybrid electric vehicle with a simplified hybrid drivetrain mechanism. These mild hybrid electric vehicles use an integrated starter–generator to assist the internal-combustion engine simply rather than to drive the vehicle independently of the internal-combustion engine. In a previous study, a lookup- table-based control scheme was proposed for optimal control of the integrated starter–generator and the internal-combustion engine on a mild hybrid vehicle. In order to investigate further the optimality of the integrated starter–generator control lookup table, a widely used global optimization technique called a genetic algorithm is utilized in this study. The constructed optimal lookup tables are implemented in MATLAB/Simulink together with a mild hybrid vehicle model, which is based on an US Environmental Protection Agency light-duty vehicle model. The simulation results show that the genetic algorithm can construct an optimal lookup table with better performance characteristics than the weighted cost function method.